Mamoncillo (Genip) Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS-1070, a 7-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing mamoncillo (genip) in the home landscape. Tables include suggested cultural practices by month, suggested fertilizer program and nutritional values. Published by the UF Department of Horticultural Sciences, November 2006.